A genetically engineered Escherichia coli strain overexpressing the nitroreductase NfsB is capable of producing the herbicide D-DIBOA with 100% molar yield - Maria Elena de la Calle; Gema Cabrera; Domingo Cantero; Antonio Valle; Jorge Bolivar (Microbial Cell Factories, 2019)
Abstract Background The use of chemical herbicides has helped to improve agricultural production, although its intensive use has led to environmental damages. Plant allelochemicals are interesting alternatives due to their diversity and degradability in the environment. However, the main drawback of this option is their low natural production, which could be overcome by its chemical synthesis. In the case of the allelochemical DIBOA ((2,4-dihydroxy-2H)-1,4-benzoxazin-3(4H)-one), the synthesis of the analogous compound D-DIBOA (2-deoxy-DIBOA) has been achieved in two steps. However, the scale up of this synthesis is hindered by the second step, which uses an expensive catalyst and is an exothermic reaction, with hydrogen release and a relatively low molar yield (70%). We have previously explored the “Green Chemistry” alternative of using E. coli strains overexpressing the nitroreductase NfsB as a whole-cell-biocatalyst to replace this second step, although the molar yield in this case was lower than that of the chemical synthesis. Results In this work, we engineered an E. coli strain capable of carrying out this reaction with 100% molar yield and reaching a D-DIBOA concentration up to 379% respect to the highest biotransformation yield previously reported. This was achieved by a screening of 34 E. coli mutant strains in order to improve D-DIBOA production that led to the construction of the ΔlapAΔfliQ double mutant as an optimum genetic background for overexpression of the NfsB enzyme and D-DIBOA synthesis. Also, the use of a defined medium instead of a complex one, the optimization of the culture conditions and the development of processes with several substrate loads allowed obtaining maxima yields and concentrations. Conclusions The high yields and concentrations of D-DIBOA reached by the microbial-cell-factory approach developed in this work will facilitate its application to industrial scale. Also, the use of an optimized defined medium with only an organic molecule (glucose as carbon and energy source) in its composition will also facilitate the downstream processes.